Inhibition of Phase Segregation in Cesium Lead Mixed-Halide Perovskites by B-Site Doping - Daocheng Hong (iScience, 2020)
Summary: The emergence of all-inorganic halide perovskites has shown great potential in photovoltaic and optoelectronic devices. However, the photo-induced phase segregation in lead mixed-halide perovskites has severely limited their application. Herein, by real-time monitoring the photoluminescence (PL) spectra of metal mixed-halide perovskites under light irradiation, we found that the photo-induced phase transition can be significantly inhibited by B-site doping. For pristine mixed-halide perovskites, an intermediate phase of CsPbBrxI3-x can only be stabilized under low excitation power. After introducing Sn2+ ions, such intermediate phase can be stabilized in nitrogen atmosphere under high excitation power and phase segregation can be started after the exposure in oxygen due to oxidization of Sn2+. Replacing Sn2+ by Mn2+ can further improve the intermediate phase's tolerance to oxygen proving that B-site doping in perovskites structure by Sn2+ or Mn2+ could effectively minimize the light-induced phase segregation and promote them to serve as promising candidates in photovoltaic and light-emitting devices.